War as a factor in the progress of civilization - James, Evan (My University, 1904)
Introduction: The most prominent feature that arrests the attention of the student in history, in studying the rise and downfall of a country or countries, is their wars and and their effect on those countries. Those who have not inquired carefully into the significance of the great wars of the past are prone to prejudice their minds so they can see only the horrors and and disasters connected with war. This is, I think, a wrong attitude to take, because a prejudiced mind cannot be expected to be fair to both sides of a question. The paramount controversies of all ages and of all degrees of civilization have appealed to war for their final decision. It would be rash in the extreme to state that war in itself is an imperative requirement to a high degree of civilization, but as long as human nature remains as it is, antagonistic and jealous, it will be a necessary factor in bringing about any new movement towards higher civilization.
Citation: James, Evan. War as a factor in the progress of civilization. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: War; Civilization; Impact of War on Civilization; Theses; Manuscripts (documents)